Feasibility of robotic pancreaticoduodenectomy. Issue 7 (3rd May 2013) - Boggi, U.; Signori, S.; De Lio, N.; Perrone, V. G.; Vistoli, F.; Belluomini, M.; Cappelli, C.; Amorese, G.; Mosca, F.
<x xml:space="preserve">Abstract</x> Background Laparoscopic pancreaticoduodenectomy is feasible, but requires adaptations to established surgical techniques. The improved dexterity offered by robotic assistance provides the opportunity to see whether laparoscopic pancreaticoduodenectomy can be performed safely when faithfully reproducing the open operation. Methods Patients were selected for robotic pancreaticoduodenectomy when generally suitable for laparoscopy. Obese patients were excluded, and those with pancreatic cancer were highly selected. A prospectively designed database was used for data collection and analysis. Results Of 238 patients undergoing pancreaticoduodenectomy, 34 (14·3 per cent) were operated on robotically. No procedure was converted to conventional laparoscopy or open surgery, despite three patients requiring segmental resection of the superior mesenteric/portal vein and reconstruction. The mean duration of operation was 597 (range 420–960) min. The mean number of lymph nodes retrieved and analysed from patients with neoplasia was 32 (range 15–76). Four patients required blood transfusions and five developed postoperative complications exceeding Clavien–Dindo grade II. There were four grade B pancreatic fistulas. One patient died on postoperative day 40. Excess mean operative cost compared with open resection was €6193. Conclusion Selected patients can safely undergo robotic pancreaticoduodenectomy. The main downsides are high costs and prolonged operating times compared with open resection.